Peningkatan Kesadaran dan Budidaya Tanaman Obat Keluarga sebagai Solusi Kesehatan Alami - Ni Wayan Lasmi; Komang Widhya Sedana Putra P (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: TOGA medicinal plants have been utilized for a long time as a traditional remedy for health in traditional communities. Their utilization has declined due to ignorance and expertise in cultivation. In South Denpasar, the majority of residents are unaware of the benefits and proper method of cultivation of TOGA. This community program seeks to introduce and promote the cultivation of TOGA as part of life. Objective: The objective of this program is to enhance community education and competency in cultivating and harvesting TOGA and, thereby, encourage greater participation in preserving traditional medicinal plants. Method: This activity was done by practice and socialization. The activities included an educational class on TOGA benefits and agricultural practice, followed by planting demonstration by facilitators and mass planting by participants. The activity lasted one day with involvement of local people, farmer associations, and academic facilitators. Result: The results showed an improvement in knowledge and ability among participants to cultivate and use TOGA. Initially, families were not familiar with TOGA and did not possess medicinal plants within their homes. After the program, the majority of participants initiated cultivating TOGA in their households and were also more responsive to its health benefits. The project also contributed towards environmental sustainability due to the initiation of green patches. Conclusion This community outreach program was able to enhance public knowledge and expertise in TOGA cultivation and use as a natural health option